2008
DOI: 10.3177/jnsv.54.511
|View full text |Cite
|
Sign up to set email alerts
|

Acute D-Psicose Administration Decreases the Glycemic Responses to an Oral Maltodextrin Tolerance Test in Normal Adults

Abstract: Summary An examination was conducted to verify D -psicose suppressed the elevation of blood glucose and insulin concentration in a dose-dependent manner under the concurrent administration of maltodextrin and D -psicose to healthy humans. Twenty subjects aged 20-39 y, 11 males and 9 females were recruited. A load test of oral maltodextrin was conducted as a randomized single blind study. The subjects took one of five test beverages (7.5 g D -psicose alone, 75 g maltodextrin alone, 75 g maltodextrin ϩ 2.5, 5 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 7 publications
4
119
0
Order By: Relevance
“…The rare sugar d-psicose is the C-3 epimer of d-fructose, has 70% of relative sweetness but only 0.3% of energy of sucrose [8,9], and has been approved as Generally Regarded as Safe (GRAS) by U.S. Food and Drug Administration (DFA). It has enormous physiological benefits including blood glucose suppressive property [10], neuroprotective effect [11], reactive oxygen species scavenging activity [12], and anti-obesity effect [13,14]. In addition, d-psicose has been considered to be able to improve food quality, for examples, it increases the gelling property and produces higher antioxidant activity and pleasant flavor through Maillard reaction with food proteins [15], and it facilitates melting of the crystalline structure in rice flour upon heating and inhibits re-crystallization during http storage [16].…”
Section: Introductionmentioning
confidence: 99%
“…The rare sugar d-psicose is the C-3 epimer of d-fructose, has 70% of relative sweetness but only 0.3% of energy of sucrose [8,9], and has been approved as Generally Regarded as Safe (GRAS) by U.S. Food and Drug Administration (DFA). It has enormous physiological benefits including blood glucose suppressive property [10], neuroprotective effect [11], reactive oxygen species scavenging activity [12], and anti-obesity effect [13,14]. In addition, d-psicose has been considered to be able to improve food quality, for examples, it increases the gelling property and produces higher antioxidant activity and pleasant flavor through Maillard reaction with food proteins [15], and it facilitates melting of the crystalline structure in rice flour upon heating and inhibits re-crystallization during http storage [16].…”
Section: Introductionmentioning
confidence: 99%
“…Matsuo and Izumori (2009) clarified the mechanism of glucose suppression in animal experiments caused by the inhibition of α-glycosidase and presumed that D-psicose had similar behavior to D-fructose in its glucose uptake from liver. Further, it was reported that D-psicose could significantly suppress the blood glucose elevation in glucose loading study on healthy adults (Iida et al 2008;Hayashi et al 2010). It was also suggested that supplemental D-psicose in the diet reduced postprandial glycemic response and improved insulin sensitivity and glucose tolerance (Hossain et al 2011).…”
Section: D-psicosementioning
confidence: 96%
“…5 suppresses glycemic responses after carbohydrate ingestion in rats. Furthermore, Iida et al [6] and Hayashi et al [7] demonstrated that D-psicose administration decreased the glycemic response to an oral maltodextrin test in normal adults. In addition, D-tagatose inhibits small intestinal disaccharidases as well as that documented for D-psicose [8,9].…”
Section: Introductionmentioning
confidence: 97%